Herramienta Google drive y su influencia en el proceso del aprendizaje de la asignatura de computación en los estudiantes del bachillerato general unificado de la unidad educativa “Milenio Simón Bolívar” de la parroquia Pimocha, del cantón Babahoyo, provincia de los Ríos. - Velastegui Balladares, Pedro Ángel (2017)
Drive helps you find relevant information, images, maps and bibliography, which you can include in a document from the same interface. It is an extension of the Google search engine that allows you to browse the web from within the same window in which you are writing the document. It is characterized by its ease of use and its simple design. Its management is intuitive; most of the actions are similar to the actions of the most common office programs. It has an internal search engine within the documents and a spell checker. There are currently multiple services that include, besides cloud storage, free web office applications, among the most popular are Google Drive, Skype Drive, among others. These services include office suites and tools Learning is the process of acquiring knowledge, skills, values and attitudes, made possible through study, teaching or experience. This process can be understood from different positions, which implies that there are different theories linked to the fact of learning. Behavioral psychology, for example, describes learning according to the changes that can be observed in the behavior of a subject. It is the fundamental process in learning is imitation (the repetition of an observed process, which involves time, space, skills and other resources). In this way, children learning.